High-Volume Hydrodissection: Assessment of Deep Inferior Epigastric Perforator Flap Perfusion Using Laser Doppler. Issue 6 (December 2015) - Fanzio, Paolo Maria; Cheng, Ming-Huei; Samcam, Ivan; Lin, Yu-Te; Gorantla, Vijay; Lee, Bernard T.; Singhal, Dhruv
Abstract : Abstract: High-volume hydrodissection of intramuscular perforators of deep inferior epigastric perforator (DIEP) flaps in Sprague-Dawley rats has previously demonstrated a significant reduction in dissection time while simultaneously increasing the safety of dissection. However, increasing volumes of fluid injected into the closed rectus compartment may have adverse consequences on perfusion to the overlying flap. A prospective experimental animal study was performed to define a safe upper limit of volume injection for high-volume hydrodissection. Eight Sprague-Dawley rats underwent bilateral "DIEP" flap dissections with varying volumes of fluid (1, 3, 6, and 9 mL) injected into the study side. The primary outcome measurement was overlying tissue perfusion, measured using laser Doppler imaging, at 6 separate time points during the flap harvest. Although no significant difference in perfusion was noted between study and control sides despite increasing volumes of injection, a trend toward significant altered perfusion was noted immediately after injection in the 9-mL study group. Six milliliters is defined as the safe upper limit volume of injection into the closed rectus compartment without significantly altering overlying flap perfusion in our Sprague-Dawley rats. Using volumetric analysis, these data translate to 425 mL as the safe upper limit for high-volume hydrodissection for a single average sized human rectus sheath during DIEP flap harvesting. The mechanical and potentially pharmacologic implications of these data in humans remain to be seen.